STRENGTH INTEGRITY ANALYSIS FOR GAS PIPELINE PASSING ACTIVE FAULT AREA CASE STUDY: GAS PIPELINE AT PORONG-SIDOARJO - AGUS SUTOPO (NIM :13104130); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja
As of today, oil and gas is still the dominant source of energy in Indonesia. Between the two, natural gas has the potential to replace oil. Even though, in its development there are many difficulties i.e. geographical problems. One of its major problems is presence of active fault between natural gas source and processing area. In this final project, the strength integrity analysis for gas pipeline at Porong-Sidoarjo has been performed. It is performed both in existing and modified pipeline route design, so that it can solve the active fault problem. The analysis is based on pipeline system modelling developed from AutoPIPE software and referred to ASME B31.8 Gas Transmission and Distribution Piping System. Loads applied in this analysis simulate the load movement caused by active fault. The modified pipeline route design results in better strength integrity on the following fault type: normal fault, reverse fault, and thrust fault. It is able to withstand land movement before failure up to 3.0541 m (stress ratio 0.99) for normal fault case, 1.0180 m (stress ratio 0.95) for reverse fault case, and 0.0365 m (stress ratio 0.75) for thrust fault case.